THE EFFECT OF FOREIGN DIRECT INVESTMENT (FDI) AND EXPORTS ON ECONOMIC GROWTH IN EAST NUSA TENGGARA (NTT) PROVINCE DURING THE PERIOD 2010–2024: A VECM APPROACH - Fransisco X Lay; Maria Indriyani H. Tiwu; Rikhard T. C. Bolang; Fransina W. Ballo (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze the long-run relationship, effects, and dynamic interactions between Foreign Direct Investment (FDI), exports, and economic growth in East Nusa Tenggara (NTT) Province during the period 2010–2024. The research employs a quantitative approach using the Vector Error Correction Model (VECM) based on quarterly secondary data obtained from the Central Bureau of Statistics (BPS) and the Ministry of Investment/BKPM. The results indicate the existence of a long-run relationship among FDI, exports, and economic growth. Partially, FDI has a significant negative effect on economic growth with a coefficient of -0.057630, while exports have no significant effect. The findings also reveal that there is no strong causal relationship among the variables, and the adjustment process toward long-run equilibrium tends to occur slowly, as indicated by the Error Correction Term (ECT) value of -0.130392. In addition, the contribution of FDI and exports to economic growth remains relatively low compared to domestic factors. These findings suggest that the role of FDI and exports in promoting economic growth in NTT has not been optimal due to structural constraints such as low value-added production, weak sectoral linkages, and limited infrastructure.